The effect of using rebound exercises on the special endurance of the 400-meter freestyle event for juniors - Kadhom Ahmed, Emad; AbdulrazzaqJabara, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
All exercises in sports have a benefit if they are based on scientific foundations, and rebound exercises occupy an important place in scheduling training for athletics to reach achievement, especially short events, including 400 meters and the achievement of a 400-meter run. Thus, this research makes a serious contribution to overcoming many field obstacles as a result of low numbers in this effectiveness at the local level. As for the research objectives, it was to develop suggested exercises to develop the endurance of special speed and to complete the 400-meter freestyle run among the members of the research sample, knowing the effect of these exercises in developing the endurance of special speed and the achievement of the 400-meter freestyle run among the members of the research sample. Among the most important conclusions reached by the researchers are: The methods of working using the proposed rebound exercises led to the development of endurance and special speed and the achievement of the 400-meter freestyle run among the members of the experimental group.